Studi Literatur: Disfungsi Seksual pada Pasien dengan Penyakit Ginjal Kronik Yang Menjalani Hemodialysis - Hardianti, Suci; Jundiah, R. Siti; Muliani, Rizki (Mando Care Jurnal, 2023)
One of the effects of chronic kidney disease is a decrease in sexual function due to long hemodialysis, where patients who undergo hemodialysis for a long time will experience an inability to enjoy sexual activity so that it has an impact on fulfilling their needs. sexuality and change the patient's sexuality pattern. Sexual dysfunction in female hemodialysis patients causes increased pain in women (dyspareunia) and difficulty in vaginal mucus, whereas in men it includes disorders of sexual desire, erectile dysfunction and premature ejaculation. The aim of this study was to review the extent of sexual function in chronic kidney disease patients undergoing hemodialysis. This type of research uses a Literature Review (LR) with a population of 69 journals, with a sample of 2 national journals and 13 international journals according to the inclusion criteria of international or national journals related to sexual dysfunction in hemodialysis patients, journals published in a span of 10 years (2010 - 2020) ) and the journal must be in full text. Evaluation of the feasibility of the data using the Joanna Brigs Institute (JBI) by filling in the critical appraisal tool checklist sheet. The results showed sexual dysfunction that occurs in men is found; dissatisfaction, avoidance, loss of energy, premature ejaculation and erectile dysfunction, impotence, does not last long during sexual activity, lack of excitement, and the condition of sperm mixed with blood. Whereas in women it is found; dissatisfaction, orgasm, decreased desire, lubrication, pain during intercourse, reluctance to engage in sexual activity, decreased desire and libido. It is hoped that this research will serve as a theoretical basis in the nursing process both applied and theoretically.